Ataxia due to injury of the cortico-ponto-cerebellar tract in patients with mild traumatic brain injury. Issue 48 (3rd December 2021) - Jang, Sung Ho; Lee, Han Do
Abstract: Introduction: The cortico-ponto-cerebellar tract (CPCT) is involved in coordination of movement; injury of the CPCT can therefore be accompanied by ataxia. In this study, using diffusion tensor tractography (DTT), we investigated injury of the CPCT in patients with mild traumatic brain injury (TBI). Methods: We recruited 45 consecutive patients with ataxia following mild TBI and 20 normal control subjects. The score of assessment and rating of ataxia (SARA) was used to evaluate of ataxia. The patients were classified into 2 groups based on the SARA; patient group A had with post-traumatic ataxia and patient group B had without post-traumatic ataxia. The fractional anisotropy (FA) value and fiber number (FN) of the CPCT was measured. Results: Significant differences were observed in the FA and FN values of the CPCT between patient group A and the control group and between patient groups A and B ( P < .05). In addition, a significant difference was observed in the FA value only of the CPCT between patient group B and the control group ( P < .05). However, no significant difference was observed in the FN value of the CPCT between patient group B and the control group ( P > .05). Conclusion: By using DTT, injury of the CPCT was demonstrated in patients who showed ataxia following mild TBI. These results suggest that DTT would be useful for evaluation of the CPCT in patients with ataxia after mTBI because mTBI usually does not show any abnormalities on conventional brain MRI.